KESESUAIAN LAHAN UNTUK KOMODITAS UNGGULAN PERTANIAN DI KABUPATEN LABUHANBATU UTARA - Regan Leonardus Kaswanto; Ruth Mevianna Aurora; Doni Yusri; Sofyan Sjaf; Simon Barus (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2021)
As an expansion area, North Labuhanbatu District has a purpose to improve the social welfare. Meanwhile one of the significant sector in the community is agriculture. Agriculture provides the highest income for the society and has a potency to further develop and establish the area. However, the development should relevant with environment characteristic essentially. Based on preliminary survey, there are 5 agricultural commodities growing in this area namely palm oil, rubber, rice field, cocoa, and coconut which spread over the 8 sub-districts. The increasing of population triggers land use changes particularly in agriculture. Therefore analysis of land suitability for agriculture is fundamental hence policy direction can be applied in each sub-district based on agriculture commodities which suitable with their characteristic accordingly. The evaluation of land suitability is conducted by comparing the physical characteristics with the existing of land suitability criteria which prossessed by ArcGIS software. Land suitability in North Labuhanbatu is identified with 4 clases: S1 (very suitable), S2 (moderately suitable), S3 (marginally suitable), and N (not suitable). Furthermore, there are 4 limiting factors in this study: water availability, root media, nutrient retention, and erosion hazards. The result shows that rubber, rice field, and coconut have very suitable (S1) land to be planted.Therefore the recomendation is to develop agroforestry landscape practices for sustainable livelihoods in Labura District.